2019
DOI: 10.1002/jsfa.10025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of linseed oil oleogels to partially replace pork backfat in fermented sausages

Abstract: BACKGROUND: Nowadays, fat replacement in meat products is a matter of concern in the meat industry. The objective of this study was to evaluate the replacement of pork backfat with two oleogels of linseed in dry-cured sausages. RESULTS: Five batches of dry-cured sausages were prepared with two oleogels, a mixture of -oryzanol and -sitosterol (SO) and beeswax (B), at two levels of replacement (20% and 40%) (SO-20, SO-40, B-20, and B-40, respectively) and a control batch. The fatty acid profile improved in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
49
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 54 publications
(67 reference statements)
17
49
1
1
Order By: Relevance
“…Thus, the fat reduction between CON and reformulated samples were about 13–14%. Our values were similar to those reported for similar dry-fermented sausages [ 12 , 20 , 56 ]. As expected, the replacement of pork backfat, which contained about 80% of total fat [ 63 ], by oil-in-water emulsions that had only 37.2% of oil resulted in a significantly decrease of fat in the reformulated samples.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the fat reduction between CON and reformulated samples were about 13–14%. Our values were similar to those reported for similar dry-fermented sausages [ 12 , 20 , 56 ]. As expected, the replacement of pork backfat, which contained about 80% of total fat [ 63 ], by oil-in-water emulsions that had only 37.2% of oil resulted in a significantly decrease of fat in the reformulated samples.…”
Section: Resultssupporting
confidence: 91%
“…The moisture values found in the control samples were similar to those reported by other authors, who found moisture values about 34–45% in dry-fermented sausages [ 30 , 54 ]. In a similar way, the moisture values of experimental batches agree with those described by other authors (around 25–30%) also in dry-cured sausages [ 20 , 27 , 36 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Franco et al [86] Olive oil gelled with soy protein concentrate and mineral water andreplacing 15%, 25%, 35%, 45%, and 55% of the pork meat…”
Section: Pastrymentioning
confidence: 99%